Status Hukum Karya Intelektual yang Dihasilkan oleh Kecerdasan Buatan dalam Rezim Hukum Paten Indonesia - Anggi Purnama Tradesa; Lalu Mariawan Alfarizi (Fakultas Hukum Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2025)
This study aims to analyze the legal status of intellectual works produced by artificial intelligence in the Indonesian patent law regime through a normative legal approach, as well as determining the legitimate patent holder for inventions produced by artificial intelligence when human contribution to the invention process is minimal or indirect. This study uses a normative legal method, which views law as written norms in legislation and legally binding behavioral guidelines. The research approach includes a legislative approach and a conceptual approach. Primary, secondary, and tertiary legal materials are processed through inventory, classification, and systematics to facilitate analysis. The analysis is carried out by applying grammatical, systematic, and teleological legal interpretations, and using legal theory and principles as analytical tools to assess the form and mechanism of legal protection. The research results indicate that the analysis and discussion outlined above can lead to the conclusion that Indonesia's patent law regime, which still requires inventors to be human legal subjects, is not fully capable of guaranteeing legal certainty for inventions produced by artificial intelligence. The concept of inventor in Law Number 13 of 2016 concerning Patents still relies on an anthropocentric paradigm, which links inventions directly to human cognitive abilities and legal responsibilities.